Anti-epidemic effectiveness of sanitary and educational work with contingents at risk of plague infection in the Gorno-Altai high-mountain natural plague center - E. V. Kuklev; V. P. Toporkov; A. I. Mischenko; V. A. Safronov; A. V. Ivanova; A. N. Matrosov; M. V. Pospelov; I. G. Karnauhov (Журнал инфектологии)
Objective is to reduce the risk of infection of people with plague in the territory of a natural focus on the basis of the targeted public health educational work with risk groups.Materials and methods. In 2017, 30 visits were made by epidemiological groups to livestock farms in the epizootic zone to inform the population about the existing risks of plague infection and to conduct interviews to assess the level of alertness regarding the risk of the disease. Work was carried out with risk contingents with coverage of 1652 people (81% of the total number of people living in livestock camps).Results. It was found that 64% of the respondents knew about the danger of plague infection in the region. 91% are aware of the role of marmots in infecting people with plague. 96.3% of respondents are aware of the ban on hunting groundhogs, while 39% continue to prey upon the grey (Altai) groundhog. The identified gaps in the population’s alertness regarding the risk of plague infection were eliminated through active sanitary and educational work with the population.Conclusion. Direct work with the population, anti-epidemic groups, significantly affected the provision of epidemiological welfare as regards plague, which is confirmed by the absence of human plague cases in the natural focus in 2017-2019.